2015
DOI: 10.1038/srep17472
|View full text |Cite|
|
Sign up to set email alerts
|

Integration of CdSe/CdSexTe1−x Type-II Heterojunction Nanorods into Hierarchically Porous TiO2 Electrode for Efficient Solar Energy Conversion

Abstract: Semiconductor sensitized solar cells, a promising candidate for next-generation photovoltaics, have seen notable progress using 0-D quantum dots as light harvesting materials. Integration of higher-dimensional nanostructures and their multi-composition variants into sensitized solar cells is, however, still not fully investigated despite their unique features potentially beneficial for improving performance. Herein, CdSe/CdSexTe1−x type-II heterojunction nanorods are utilized as novel light harvesters for sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 62 publications
0
31
0
Order By: Relevance
“…The internal surface area of PS-mediated TiO 2 layer for various PS fractions is calculated based on a simple Monte-Carlo method [46], and the possible overlap between beads is considered rather than assuming the beads as hard-sphere. The random distribution of 200-nm spheres in 10 × 10 × 1 μm 3 volume is simulated by assuming the probability profile of sphere-to-sphere overlap to show exponential decay, the exponent of which is assumed following the Hertzian model of elastic potential energy for contact of two identical elastic spheres at a given overlap displacement [47].…”
Section: Resultsmentioning
confidence: 99%
“…The internal surface area of PS-mediated TiO 2 layer for various PS fractions is calculated based on a simple Monte-Carlo method [46], and the possible overlap between beads is considered rather than assuming the beads as hard-sphere. The random distribution of 200-nm spheres in 10 × 10 × 1 μm 3 volume is simulated by assuming the probability profile of sphere-to-sphere overlap to show exponential decay, the exponent of which is assumed following the Hertzian model of elastic potential energy for contact of two identical elastic spheres at a given overlap displacement [47].…”
Section: Resultsmentioning
confidence: 99%
“…Luo et al used chemical vapor deposition to associate CdS, CdSe or CdSeS rods to TiO 2 NRs arrays and demonstrated that the CdSeS/TiO 2 heterostructure exhibits the highest performances as photoelectrode [39]. More recently, small CdSe NRs [40] or type II CdSe/CdSe x Te 1− x NRs [41] were also used as light harvesters to develop TiO 2 -based solar cells. Core/shell TiO 2 /CdSe NRs were also prepared by growing CdSe quantum dots onto TiO 2 NRs at high temperature [42].…”
Section: Introductionmentioning
confidence: 99%
“…Until now, a wide spectrum of semiconductor nanomaterial-based epitaxial heterostructures with varying architectures and compositions has been prepared by wet-chemical methods. These nanomaterials with unique optical and electric properties have shown many potential applications, including light-emitting devices (LEDs) [152][153][154], solar cell [155][156][157], photodetectors [110], bio-imaging/sensing [158], and catalysis [33,35]. In this section, we will briefly introduce the unique advantages of epitaxial heterostructures prepared via wet-chemical methods in some promising applications.…”
Section: Properties and Applications Of Semiconductor Nanomaterial-bamentioning
confidence: 99%